PENGARUH KOMBINASI PENGATUARAN JARAK TANAM DAN PEMBERIAN PUPUK KOMPOS TERHADAP PERTUMBUHAN DAN HASIL TANAMAN HANJELI PULUT (COIX LACRYMA JOBI L.) DI DATARAN RENDAH INDRAMAYU - Maswindra, Maswindra; Surawinata , Tadjudin; Purnomo, Dwi (Prodi Agronomi Pascasarjana Universitas Swadaya Gunung Jati, 2022)
The aims of the experiment were to determine the effect of the Combination of plant spacing and Compost Fertilizer dosage on Growth and Yield of Job’s Tears (Coix lacryma-jobi L.) in lownlands Indramayu.. The experiment was carried out in Mekarjaya Village, Gantar District, Indramayu Regency, West Java. The time of the research was carried out from August to January 2022. The location is located at an altitude of ± 50 m above sea level (masl), the soil type is the association of Latosol and Regosol, including type D rain (moderate). The experimental method used was an experimental method with a randomized block design (RBD). The treatments given were a combination dose of compost, and plant spacing so that there were 12 treatment combinations where each treatment got 3 replications so that 36 experimental plots were obtained. The first factor is compost consisting of 3 levels, (K1: 10 tons / ha, K2: 15 tons / ha, and K3: 20 tons / ha), the second factor is the spacing of plants consisting of 4 levels, jajar legowo 2:1 ( 100 cm x 50 cm ) x 30 cm) 2 seeds/hole, jajar legowo 2:1 (100 cm x 40 cm ) x 30 cm) 2 seeds/hole, zig-zag (100 cm x 50 cm) x 30 cm) 2 seeds/hole) and zig-zag (100 cm x 40 cm) x 30 cm) 2 seeds/hole). The experimental results showedThe results showed that (1) The combination of plant spacing and compost fertilizer had a significant effect on seed weight per plot, but had no significant effect on plant height, number of tillers per clump, number of leaves, number of side branches, root volume, plant biomass, number of pithy seeds per panicle. and number of empty seeds per mala, weight of 100 seeds, weight of seeds per clump, and harvest index. (2) The highest seed weight per plot was produced by a combination of 50 cm x 100 cm spacing and 15 tons/ha of compost fertilizer at 3260 kg per plot or equal to 3.26 tons/ha. This treatment was not significantly different from the 50 cm x 100 cm spacing and 20 ton/ha compost, but was significantly different from the other treatment combinations.(3) There was a significant correlation between plant height and seed weight per plot in the period 7 WAP and 9 WAP in low category and there was a significant correlation between the number of tillers per clump and seed weight per plot in all observation periods in the low, strong, and medium category.